Follow-up Testing for Hepatitis C Virus Infection: An Analysis of Massachusetts Surveillance Data, 2007–2010. (September 2014) - Barton, Kerri; Church, Dan; Onofrey, Shauna; Cocoros, Noelle; DeMaria, Alfred
The Massachusetts Department of Public Health (MDPH) identified cases of hepatitis C virus (HCV) infection reported from 2007 through 2010 to assess evidence of appropriate follow-up testing for the diagnosis of active HCV infection. Surveillance data were used to assess the number of people with reported HCV who had an antibody test and nucleic acid test (NAT) for HCV, to determine the time between tests, and to identify demographic characteristics. Out of the 34, 005 cases of HCV reported with laboratory results during the study period, 45% ( n =15, 279) had only an antibody test reported and 55% ( n =18, 726) had a NAT reported, with differences by age, gender, and region of residence. Nearly half of those with reported cases of HCV infection in Massachusetts did not have a NAT reported to MDPH, indicating that these individuals may not have received appropriate diagnostic testing. Analysis of demographics suggests differences by age, gender, and region.